Blood and Marrow Transplant Clinical Trials Network Study 1102 heralds a new era in hematopoietic cell transplantation in high‐risk myelodysplastic syndromes: Challenges and opportunities in implementation. Issue 23 (10th August 2021) - Warlick, Erica D.; Ustun, Celalettin; Andreescu, Astrid; Bonagura, Anthony F.; Brunner, Andrew; Chandra, Abhinav B.; Foran, James M.; Juckett, Mark B.; Kindwall‐Keller, Tamila L.; Klimek, Virginia M.; Pease, Daniel F.; Steensma, David P.; et al.
Abstract : Lay Summary: People who have advanced myelodysplastic syndromes (MDS) may live longer if they get a bone marrow transplant (BMT) instead of other therapies. However, only 15% of people with MDS actually get BMT. Experts say community physicians and transplant physicians should team up with insurance companies and patient advocacy groups to 1) spread this news about lifesaving advances in BMT, 2) ensure that everyone can afford health care, 3) provide emotional support for patients and families, 4) help patients and families get transportation and housing if they need to travel for transplant, and 5) improve care for people of under‐represented racial and ethnic backgrounds. Abstract : Blood and Marrow Transplant Clinical Trials Network Study 1102 demonstrates superior survival for patients with high‐risk myelodysplastic syndromes undergoing allogeneic hematopoietic cell transplantation compared to nontransplant therapies. The article describes a framework to expand access to transplantation for patients with high‐risk myelodysplastic syndromes to ensure optimal implementation of the results of this study.